Kematian janin dalam kandungan pada ibu hamil dengan infeksi sifilis laten: laporan kasus - Hani Lusyana; Lina Damayanti; Agus Walujo (DiscoverSys Inc., 2021)
Background: Pregnant women and newborns are a group that is prone to contracting sexually transmitted infections, although they do not directly engage in high-risk sexual behavior. One that has an unexpected impact on pregnant women and newborns is syphilis by the bacterium Treponema pallidum. Transmission of syphilis from mother to fetus is usually worse when the infection in pregnant women is not detected or not appropriately treated early in pregnancy. This case report aims to evaluate fetal death in the womb in pregnant women with latent syphilis infectionCase Presentation: A 19-year-old pregnant woman aged 31-32 weeks diagnosed with late postpartum spontaneous Intrauterine Fetal Death (IUFD) with early latent syphilis. The diagnosis of syphilis was made based on the Veneral Disease Research Laboratory (VDRL) serological test (1:64), Treponema Pallidum Hemagglutination Assay (TPHA) (1:1,280), and without any mucocutaneous complaints. The patient received Benzathine Penicillin G 2.4 million IU single dose intramuscularly. The diagnosis of IUFD was made one day after the administration of therapy and the baby was born with multiple congenital abnormalities.Conclusion: Undiagnosed and adequately treated syphilis in pregnant women can result in perinatal death caused by multiple congenital abnormalities. Latar Belakang: Ibu hamil dan bayi baru lahir merupakan kelompok rawan tertular infeksi menular seksual, walaupun tidak secara langsung berperilaku seksual resiko tinggi. Salah satu yang memiliki dampak kelahiran yang tidak diharapkan pada ibu hamil dan bayi baru lahir adalah Sifilis oleh bakteri Treponema pallidum. Transmisi sifilis dari ibu ke janin biasanya berakibat buruk ketika infeksi pada ibu hamil tidak terdeteksi atau tidak diobati secara benar di awal kehamilan. Laporan kasus ini bertujuan mengevaluasi kematian janin dalam kandungan pada ibu hamil dengan infeksi sifilis latenPresentasi Kasus: Seorang wanita hamil berusia 19 tahun usia kehamilan 31-32 minggu dengan diagnosis akhir postpartum spontan Intrauterine Fetal Death (IUFD) dengan sifilis laten dini. Diagnosis sifilis ditegakkan berdasarkan tes serologis Veneral Disease Research Laboratory (VDRL) (1:64), Treponema Pallidum Hemagglutination Assay (TPHA) (1:1.280), dan tanpa adanya keluhan mukokutaneus. Pasien mendapatkan terapi Benzatin Penisilin G 2.4 juta IU single dose secara intramuskular. Diagnosis IUFD ditegakkan satu hari setelah pemberian terapi dan bayi yang dilahirkan memiliki kelainan kongenital multipel.Kesimpulan: Sifilis pada ibu hamil yang tidak terdiagnosis dan diterapi dengan adekuat dapat mengakibatkan terjadinya kematian perinatal yang disebabkan oleh kelainan kongenital multipel.